AKHLAK SEBAGAI AZAS KEBAHAGIAAN KELUARGA DAN MASYARAKAT - Aliasan Aliasan (Wardah, 2015)
This research entitles attitude as the base for family and society happiness which aims to express Islam concept in positioning the attitude and its implication. They are wife attitude, husband, neighbor, and society and also their duties. Referring to Al-Quran and Hadist, attitude gives implication to reach happiness to the family and becomes the guidelines to human activities, individually or in groups. Having a good attitude is an effortto reachteh happiness for family and societies.